2008
DOI: 10.1590/s1413-70542008000300031
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de custos como ação de competitividade: estudo de um caso na avicultura de corte

Abstract: Trata-se no presente trabalho de um estudo de caso, tendo sido desenvolvido com o objetivo de mostrar a importância do gerenciamento de custos como ação de competitividade da empresa agropecuária. Para tal, foram calculados os custos de produção e a posterior apuração do resultado de um ciclo de produção de uma empresa produtora de frango de corte. As informações utilizadas nos cálculos foram extraídas da contabilidade gerencial da mesma. No estudo em questão, a ração e o pinto de um dia foram os principais co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
0
3
0
7
Order By: Relevance
“…The predominant use of family labor in broiler production in Southwestern Paraná is mainly related to farm size, which is predominantly small in this region. Carvalho et al (2008), in their study on broiler production costs in Western Minas Gerais, Brazil, stated that the third main cost of broiler production activities is related to labor expenses (fixed and temporary employees), which accounts for 3.61% of total broiler production costs.…”
Section: Factors That Impact the Financial Performance Of Broiler Promentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant use of family labor in broiler production in Southwestern Paraná is mainly related to farm size, which is predominantly small in this region. Carvalho et al (2008), in their study on broiler production costs in Western Minas Gerais, Brazil, stated that the third main cost of broiler production activities is related to labor expenses (fixed and temporary employees), which accounts for 3.61% of total broiler production costs.…”
Section: Factors That Impact the Financial Performance Of Broiler Promentioning
confidence: 99%
“…The remaining identified problems related to broiler farming in Southwestern Paraná included the low quality of drinking water and bedding material; stocking density; labor issues; low market prices of chicken meat; power outage, which stops the operation of environmental-control systems; and high production costs, due to the high prices of wood to feed the brooders during the winter and high expenses with electricity to run the ventilation fans during the summer. Carvalho et al (2008) reported that the high electricity costs accounted for 1.10% of total broiler production costs in Western Minas Gerais, Brazil. Moreover, contracts between the broiler companies and the farmers do not entirely protect the farmers, who are then partially liable to the risks associated with broiler production (Figueiredo et al, 2006).…”
Section: Factors That Impact the Financial Performance Of Broiler Promentioning
confidence: 99%
“…Demonstrando assim uma real preocupação com a transparência do processo de integração entre o avicultor e a empresa. Contudo demonstra a margem de lucro da empresa, onde é possível identificar que o maior custo da produção para a mesma está relacionado a alimentação dos animais (Tabela 3), seguido da aquisição dos animais fator este que se assemelha a achados por Carvalho et al, (2008) A cadeia a jusante na empresa em questão realiza a pesagem dos animais. Quando a venda realizada é de animais vivos os mesmos são aferidos os pesos na propriedade.…”
Section: Resultsunclassified
“…In broiler production, the marketing value is an external variable, to what the administrators have little or no influence, however, monitoring the production costs and productivity rates it is essential to enhance the benefits (Carvalho;Fiúza;Lopes, 2008). Economical and financial analysis...…”
Section: Cost Productionmentioning
confidence: 99%